Factors associated with the prevalence of apical periodontitis: An observational study - Rita Noites; Maria Bartolomeu; Ana Sofia Duarte; Alejandro Perez; Miguel Cardoso (Revista Portuguesa de Estomatologia, Medicina Dentária e Cirurgia Maxilofacial)
Objectives: Apical periodontitis is a lesion of endodontic origin caused by an immune response to necrotic and infected dental pulp. Since apical periodontitis can persist after endodontic treatment, radiographic diagnosis is crucial. This study evaluates factors associated with the prevalence of apical periodontitis in a Portuguese population using the full-scale periapical index. Methods: A cross-sectional study analyzed 402 medical records and panoramic radiographs from January to May 2023. The periapical status, presence of apical periodontitis, quality of endodontic treatment, quality of coronal restoration, presence of caries lesions, and presence of retained root fragments were assessed. The correlation between these variables was examined. Results: Among 9056 teeth, 4.7% presented apical periodontitis (periapical index ≥3), and 53.3% of participants had fewer than one apical periodontitis lesion. Of 437 teeth with endodontic treatment, 300 (69.6%) did not have apical periodontitis, while 131 (30.4%) had apical periodontitis. A significant statistical relationship (p<0.05) was observed between apical periodontitis and other dental conditions, including the presence of retained root fragments, caries lesions, the quality of endodontic treatment, and the quality of restoration. The strongest correlation was found between apical periodontitis and the quality of endodontic treatment (Cramer’s V = 61%), while no consistent correlations were observed with other variables. Conclusions: The prevalence of apical periodontitis was higher in teeth with endodontic treatment, with a strong correlation with treatment quality. The presence of caries lesions, coronal restorations, and retained root fragments also influenced the occurrence of apical periodontitis, reinforcing the need for further studies.